An unknown input multiobserver based on a discrete uncoupled multimodel for uncertain nonlinear systems: Experimental validation on a transesterification reactor. (October 2019) - Messaoud, Anis; Ben Atia, Samah; Ben Abdennour, Ridha
Abstract: In the present paper, an unknown input multiobserver (UIMO) is designed for the state estimation of uncertain non-linear systems. A discrete decoupled state multimodel is exploited to describe the behavior of non-linear systems. A particular transformation of uncertainties to unknown inputs is considered. The LMI approach is used to establish the convergence conditions of the state estimation error. The efficiency of the proposed strategy is emphasized through an illustrative example and a real time application on a semi-batch reactor that lead to good performance in terms of robustness, convergence speed and precision.